Cervical cancer in Iquitos, Peru: local realities to guide prevention planning - Hunter Jennifer L. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
Cervical cancer is a major public health problem in Latin America, and in much of the underdeveloped world. This issue has not historically been addressed as a health priority, but in recent years is receiving increased attention and funding. This ethnographic study on the experience of cervical cancer was conducted in Iquitos, Peru, between August 1998 and May 1999. Research methodologies included: (1) observation and household interviews to obtain background knowledge about the region, medical systems, and local cultural understanding of illness; (2) cancer experience interviews; and (3) case studies of women in various stages of cervical cancer or diagnosis. Findings are presented related to local knowledge and experience of Pap smears and cervical cancer and the ineffectiveness of a recently initiated cervical cancer screening program. The findings guide recommendations for interventions in the region in relation to: (1) needed changes in health education, (2) screening frequency and age, (3) sites for screening and treatment, (4) type and availability of treatment, (5) payment issues, (6) documentation of care, and (7) the potential of herbal remedies.